Sensory characteristics and acceptability of rice composites as staple - Nagares, N. D. L.; Hurtada, W. A.; Dizon, E. I.; Rodriguez, F. M.; Barrion, A. S. S.; Yee, M. G. (2003)
One hundred (100) percent QPM white corn and IR 72 and their composites (9 rice and corn combinations) were evaluated of their sensory characteristics such as appearance, aroma, flavour, cohesiveness and tenderness. General acceptability test based on degree of liking was also conduced. In general, all rice composites were acceptable but 70:30 (rice to corn combination) was more acceptable. Flavour and aroma upon addition contributed to its greater acceptability. Sensory evaluation further revealed that 42% of the respondents indicated flavour as the sensory attribute affecting their choice, 29% for tenderness, 19% for color and 10% for aroma. The same rice composite was evaluated when served daily during lunch time in one food canteens in Barangay Batong Malake, Los Baños, Laguna. Almost 98% of the respondents like it. Ninety two percent (92%) of the respondents answered positively that they will buy the rice composite (70:30) and about 42% stated their willingness to buy it at P20.00 per kilo. Based on the 2002 rice importation data, substituting the consumption of rice by 10% corn grits will be enough to fill the rice shortage only if the non-corn eating Filipinos will accept rice composites as their staple. This study clearly indicated that rice composite is a potential alternative to rice alone as a staple.
Keywords: Rice; Rice--Quality; Rice -- Nutritional aspects